2009
DOI: 10.1016/j.molcel.2009.06.016
|View full text |Cite
|
Sign up to set email alerts
|

SR Proteins in Vertical Integration of Gene Expression from Transcription to RNA Processing to Translation

Abstract: Summary SR proteins have been studied extensively as a family of RNA binding proteins that participate in both constitutive and regulated pre-mRNA splicing in mammalian cells. However, SR proteins were first discovered as factors that interact with transcriptionally active chromatin. Recent studies have now uncovered properties that connect these once apparently disparate functions, showing that a subset of SR proteins seem to bind directly to the histone 3 tail, play an active role in transcriptional elongati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
275
1
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(283 citation statements)
references
References 93 publications
6
275
1
1
Order By: Relevance
“…It has been shown that depletion of SRSF2 results in genomic instability; triggering significant double stranded DNA breaks [35]. In fact, SRSF2 mutations have been associated with a higher number of mutations of other genes in comparison to other spliceosomal mutations [13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that depletion of SRSF2 results in genomic instability; triggering significant double stranded DNA breaks [35]. In fact, SRSF2 mutations have been associated with a higher number of mutations of other genes in comparison to other spliceosomal mutations [13].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the observation that exonic splicing enhancers can also alter the efficiency of mRNA translation in a position-specific manner Michlewski et al 2008;Delestienne et al 2010). Thus, an unanticipated consequence of alternative splicing may lie within the subsequent regulation of the RNA binding proteins packaged upon each isoform: functionally distinct mRNPs with distinct cytoplasmic fates (Zhong et al 2009;Wang et al 2012).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 92%
“…It is clear that the trans-acting factors associated with alternative mRNA isoforms can vary just as distinctly as the protein-coding capacities of the messages they encode. Many RNA binding proteins, including shuttling proteins, are implicated in multiple steps of posttranscriptional gene regulation, including mRNA export, stability, surveillance, localization, and translation (Sanford and Caceres 2004;Zhang and Krainer 2004;Zhong et al 2009;Han et al 2011). These factors can be transcript-associated throughout the life cycle of an mRNA and may coordinate nuclear and cytoplasmic steps of gene expression (Dreyfuss et al 2002;Nashchekin et al 2007;Kylberg et al 2008).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…However, they are also subject to splicing-dependent dephosphorylation, which promotes their tight association with the spliced mRNA. As mRNP components, SR proteins can enhance nucleocytoplasmic export, translation, and decay of their bound mRNAs [20][21][22]. Thus, as elaborated below, one means by which 5UIs and 3UIs influence gene expression is by promoting the loading of mRNP proteins with downstream functional consequences.…”
Section: Splicing Directs Mrnp Formationmentioning
confidence: 99%